EVALUASI SISTEM DISTRIBUSI AIR MINUM DI PDAM KABUPATEN BANDUNG DAERAH PELAYANAN KOTA LEMBANG (DENGAN SOFTWARE EPANET 2.0) - WININDITO, ANGGORO
EPANET is used as tool for modelling water distribution system of PDAM Kabupaten Bandung of service area of the Lembang town. Usage of Bottom-up method is more emphasized in determination node-loading and used to determine the node-loading of commercial zone, industrial zone, governance zone, social/education institution, and public hydrant, while Topdown method is used for residential zone. The best calibration is selected by comparing four adjustment; elevation, demand, elevation and demand, and also Hazen-William coefficient adjustment against pressure and flowrate to most coming near field condition. The biggest procentage adjustment and the smallest error owned by adjustment to demand added by elevation. Calibration and validation should be completed and conducted to get the more accurate time pattern curve. First simulation, leakage approach 0% and 45 % run to know the leakage influence to pressure and system velocity at certain time and got that ever greater of leakage and excelsior multiplier at time pattern cause the velocity at pipe so high and have bigger headloss even also thus as a result head pressure will smaller. The second simulation is run to know the optimal capacities of reservoir which ought to be used. The third simulation is run to know the influence of valve arrangement to the network system at the usage of reservoir and tank. The significant change of pressure and system velocity is not happened.